2002
DOI: 10.1016/s0033-3506(02)90070-3
|View full text |Cite
|
Sign up to set email alerts
|

An interim report of health needs assessment of asylum seekers in Sunderland and North Tyneside

Abstract: A health needs assessment questionnaire was developed and administered to 397 asylum seekers, 291 males and 106 females, in Sunderland and North Tyneside in the North East of England. The data from the questionnaires were analysed using SPSS Version 10. Individuals retained a copy of their own questionnaire to be used as a hand held record. There was much heterogeneity of country of origin, culture, religion and previous employment and language backgrounds within the sample. A range of health needs was identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
1
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 0 publications
0
18
1
1
Order By: Relevance
“…36,42,46 Asylum seekers' utilisation of preventative health services, such as screening, health education and immunisation, as well as dental care, allied health and other specialist services were limited or not commonly measured. The few available data suggest that less than 25% of female asylum seekers in Blackwell et al and Rogstad and Dale reported having undergone a cervical pap screening test (v. 62% reported in the host population), 29,41 and overall preventative assessment, including general check-up and health education, occurred in 1 out of 20 encounters in CorreaVelez et al's study in Australia. 31 Finally, in comparing the consumption and costs of health services by asylum seekers with a local comparable sample, Bischoff et al 27 found that the mean (AEs.d.)…”
Section: Health Service Utilisationmentioning
confidence: 94%
See 4 more Smart Citations
“…36,42,46 Asylum seekers' utilisation of preventative health services, such as screening, health education and immunisation, as well as dental care, allied health and other specialist services were limited or not commonly measured. The few available data suggest that less than 25% of female asylum seekers in Blackwell et al and Rogstad and Dale reported having undergone a cervical pap screening test (v. 62% reported in the host population), 29,41 and overall preventative assessment, including general check-up and health education, occurred in 1 out of 20 encounters in CorreaVelez et al's study in Australia. 31 Finally, in comparing the consumption and costs of health services by asylum seekers with a local comparable sample, Bischoff et al 27 found that the mean (AEs.d.)…”
Section: Health Service Utilisationmentioning
confidence: 94%
“…29,32,37,40,42 Prevalence differed between study populations, but symptoms and medical diagnoses were commonly noted for the following conditions: dental; headache or migraine; musculoskeletal; neck, back or shoulder pain; dermatological; respiratory; and gastrointestinal problems. Four studies focussed specifically on sexual and reproductive health issues.…”
Section: Physical Health Statusmentioning
confidence: 96%
See 3 more Smart Citations